Analisis Korelasi Perubahan Iklim Terhadap Kualitas Dan Kuantitas Hasil, Perubahan Teknologi Dan Pendapatan Petani Padi Di Kabupaten Manokwari (Studi Kasus Petani Di Distrik Prafi) - Dedi Riantoro; Maria Magdalena Semet (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
This study aims to analyze the correlation of climate change on the quality and quantity of yields, technological change, and rice farmers' income in Manokwari Regency (case study of farmers in Prafi District). This type of research is quantitative associative. The type of data used is primary data obtained through an observation and interview approach to rice farmers to explain the relationship of climate change to income, rice quality and technological changes made in the Prafi District of Manokwari Regency. And secondary data obtained from the Central Statistics Agency (BPS) and the Agriculture and Food Security Agency of Manokwari Regency. The data collection method uses the method of observation, interviews, questionnaires and literature methods. While the analysis method uses crosstabs analysis (cross tabulation). With the significance test using chi-square analysis. The results showed there was no correlation of climate change on the quality and quantity of yields, technological change, and rice farmers' income in Manokwari Regency.